Implementasi Augmented Reality untuk Pembelajaran Organ Tubuh Menggunakan Metode Multimedia Development Life Cycle - Dini Destiani Siti Fatimah; Bobbi Dwitama Eden Akihary (Jurnal Algoritma, 2026)
Augmented reality technology offers innovations with great potential in the field of education by enriching the learning experience for students and teachers. In classroom teaching and learning activities, teachers use supporting learning tools such as textbooks and allow students to use smartphones, as well as projector facilities to deliver material to students. These classroom learning activities have not yet utilized educational teaching aids, so instruction that remains teacher-centered and relies on projectors to display 3-dimensional images is still a dominant characteristic of the learning process. As a result, students only experience Biology learning in a 2-dimensional form, whereas understanding the shape of body organs today also needs to be presented in 3-dimensional form. This study aims to develop a human body organ learning application using augmented reality (AR) technology with the Multimedia Development Life Cycle (MDLC) method. Data were collected through user needs analysis and the design of AR elements derived from junior high school science teaching materials. The results show that this application increases students’ curiosity toward science and supports the learning process interactively. The main contribution is an innovative multimedia-based technological solution for education.